Microthin Descemet Stripping Automated Endothelial Keratoplasty Versus Descemet Membrane Endothelial Keratoplasty: A Randomized Clinical Trial. Issue 9 (September 2021) - Matsou, Artemis; Pujari, Rathin; Sarwar, Hammad; Rana, Mrinal; Myerscough, James; Thomson, Susan M.; Nandakumar, Girinath; Zhang, Jufen; Rajan, Madhavan S.
Abstract : Purpose: To compare visual outcomes, complications, and vision-related quality of life (QoL) after microthin Descemet stripping automated endothelial keratoplasty (MT-DSAEK) versus Descemet membrane endothelial keratoplasty (DMEK) for the management of corneal endothelial dysfunction in Fuchs dystrophy. Methods: This is a prospective, double-blinded randomized controlled clinical trial. Patients with visually significant endothelial decompensation from Fuchs dystrophy were prospectively randomized to receive MT-DSAEK or DMEK surgery. The primary outcome was best spectacle-corrected visual acuity (BSCVA) at 12 months. Secondary outcomes included refraction, keratometry, endothelial cell count, complications, and vision-related QoL at 6 and 12 months postoperatively. Results: A total of 56 eyes of 56 patients were enrolled, 28 in each group. Postoperatively, LogMAR mean BSCVA in the MT-DSAEK group was 0.17 ± 0.08 and 0.11 ± 0.09 at 6 and 12 months compared with 0.09 ± 0.13 and 0.04 ± 0.13 after DMEK ( P = 0.03, P = 0.002 respectively) with the DMEK cohort achieving 3.5 logarithm of the minimum angle of resolution letters better BSCVA at 1 year compared with MT-DSAEK. Complication rates were similar with 3.5% rebubbling rate in both groups, 1 primary graft failure in DMEK and a single endothelial rejection in the MT-DSAEK arm. Vision-related QoL was comparable at 6 and 12 months postoperatively, and no eyes demonstrated loss of vision from preoperative BSCVA. Conclusions: DMEK surgery resulted in significantly better BSCVA at 1, 3, 6, and 12 months postoperatively compared with MT-DSAEK. Patient satisfaction was similar with no differences reported in vision-related QoL scores, as was the complications profile between groups. Thus, our results favor DMEK as the better choice procedure for eyes with Fuchs-related corneal decompensation without ocular comorbidities.